Disability Law and Human Rights
X, 268 p. 1 illus.
Keywords: This book, exploring the theoretical and practical implications of the United Nations Convention on the Rights of Persons with Disabilities (CRPD), brings together an international and interdisciplinary group of leading researchers in the areas of philosophy of disability, disability law, and disability policy. It addresses both the philosophical foundations of the CRPD as well as complex contemporary legal and policy debates. With a comprehensive introduction outlining key milestones in the development and implementation of the CRPD, the book addresses the most fundamental questions the CRPD raises for the way we think about human rights, law, and disability, and how we operationalize rights in the legal and policy domains. The contributors traverse themes of personhood, equality, capacity, and intersectionality, explore the dilemmas involved in translating these concepts in practice, and reflect on the promises and limitations of the human rights project. Franziska Felder is Professor of Inclusive Education and Disability Research at the University of Vienna (Austria). Her work concentrates on justice in education, with a special focus on inclusive education and disability. She is, together with Jerome E. Bickenbach and Barbara Schmitz, Editor of the Cambridge University Press’s volume Disability and the Good Human Life (2014). Laura Davy is a Research Fellow at the Australia and New Zealand School of Government and the Crawford School of Public Policy at the Australian National University. She is a political theorist and social policy researcher with a longstanding interest in disability studies and the philosophy of human rights. Rosemary Kayess is Chair of the United Nations Committee on the Rights of Persons with Disabilities (CRPD) and Senior Lecturer in the Faculty of Law at the University of New South Wales. She was a designated expert on the Australian Government delegation to the United Nations negotiations for the CRPD and has held ministerial advisory roles with the Australian Government on a range of issues.